Influence of Ba2+ consumption and intermediate dwelling during processing of YBa2Cu3O7 nanocomposite films. Issue 7 (27th December 2018) - Rijckaert, Hannes; Hänisch, Jens; Pollefeyt, Glenn; Bäcker, Michael; Van Driessche, Isabel
Abstract: Achieving high‐critical current densities ( J c ) with small artificial pinning centers is a crucial challenge for YBa2 Cu3 O7− δ (YBCO) nanocomposite thin films fabricated using chemical solution deposition methods. In this work, the YBCO texture, structure purity, and its J c properties were improved by understanding the influence of preformed ZrO2 nanocrystals (Ba 2+ consumption) during the nucleation and growth mechanism. This comprehensive study leads to an additional intermediate dwelling step during thermal process to increase the YBCO nuclei density before the YBCO growth, resulting to a self‐field J c of 5‐6 MA/cm 2 at 77 K for undoped and ZrO2 ‐doped YBCO films. Counter‐intuitively, the space and size distribution of the ZrO2 nanocrystals in the YBCO matrix are independent of this intermediate dwelling step.